A call to action: Issuing a diversity and inclusion challenge to research organizations. Issue 6 (26th July 2021) - Abdel‐Rahman, Susan M.; Wimes, Michelle P.; Curran, Tom
Abstract: Individuals who identify as Black, indigenous, and people of color face well‐documented health disparities. A root cause is the lack of empiric evidence for or against the use of various treatments in their medical management. This communication proposes a new benchmarking strategy for evaluating racial and ethnic representation in clinical research that can be compared across institutions with the intent of increasing accountability for diversity and inclusion among organizations that conduct clinical research.